Processing Clam Meat into Pickles - VIJAYAN, P K; PERIGREEN, P A; SURENDRAN, P K; BALACHANDRAN, K K (Fishery Technology, 2017)
Methods have been worked out for the production of pickles from clam(Velorita sp.) meat. The bacteriological quality of the clam meat at different stagesof processing was studied. The clam pickles packed in glass bottles and sealedair tight! remained in good condition for six months at ambient temperatures.